Zirconium-based metallic glass and zirconia coatings to inhibit bone formation on titanium. (9th October 2020) - Rajan, S Thanka; V V, Anusha Thampi; Terada-Nakaishi, Michiko; Chen, Peng; Hanawa, Takao; Nandakumar, A K; Subramanian, B
Abstract: Surface-modified commercially pure titanium (Cp-Ti) with zirconium (Zr)-based thin film metallic glasses (Zr-TFMGs) and ZrO2 thin films were surgically implanted into the tibiae of rats; the bone formation was analyzed to examine the performance of the coatings as a biomaterial. Zr-TFMGs and ZrO2 thin films were coated on Cp-Ti substrates to monitor the control of assimilation in vitro and in vivo . The microstructural and elemental analyses were carried out for the as deposited thin films by x-ray diffraction (XRD), transmission electron microscopy and x-ray photoelectron spectroscopy. TFMG- and ZrO2 -coated Ti specimens were immersed in simulated body fluid (SBF) for a period of 21 days to evaluate the calcium phosphate precipitation in vitro . XRD, x-ray photoelectron spectroscopy and scanning electron microscopy/energy dispersive x-ray spectroscopy were used to quantify the mineralization on the coated Zr-TFMG and ZrO2 . In vitro corrosion studies showed that the Zr-based TFMG and ZrO2 coatings sustained in the SBF, exhibited superior corrosion resistance to the bare crystalline Ti substrate. Wettability studies showed TFMG and ZrO2 coatings with a hydrophobic nature, and the TFMG-coated SBF-submerged specimens showed a hydrophilic nature. The in vitro cell viability of MC3T3-E1 cells showed good cell proliferation and low cytotoxicity. The calcification deposits were evaluated by staining with alizarin red S, which showed a lower calcium formation on Zr-TFMG compared to ZrO2 . The present work also aims to assess the assimilation behavior of Cp-Ti, Zr-TFMG and ZrO2 in vivo by inserting the coated specimen in the femur of rats. After post-implantation of 8 weeks, specimens were examined by micro-CT evaluation. The bone contact ratios as calculated were 72.75%, 15.32% and 38.79%. Consequently, the bone affinity was Cp-Ti wire >ZrO2 -coated Ti wire >Zr48 Cu36 Ag8 Al8 -coated Ti wire.